Adolescence, culture and law in the present time. A psychoanalytic refl ection (2019)
This writing is part of some academic refl ections that theauthors have been making about the different avatars that canoccur in the psychic constitution of adolescent subjects. Thisarticle is an initial proposal of how to understand the timeevolution of the adolescent encounter with the implicationsof their sexuality, their body, their language and the differentwaivers they must live with for entering the social bond.Finally, this signifi cant moment of adolescence is articulatedwith the entrance to the culture and the implications it hastowards the encounters and/or dis-encounters with the law.